Answer:
Final result :
x + 2
—————
x - 1
Step-by-step explanation:
Step-1 : Multiply the coefficient of the first term by the constant 7 • 3 = 21
Step-2 : Find two factors of 21 whose sum equals the coefficient of the middle term, which is -10 .
-21 + -1 = -22
-7 + -3 = -10 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -7 and -3
7x2 - 7x - 3x - 3
Step-4 : Add up the first 2 terms, pulling out like factors :
7x • (x-1)
Add up the last 2 terms, pulling out common factors :
3 • (x-1)
Step-5 : Add up the four terms of step 4 :
(7x-3) • (x-1)
Which is the desired factorization
Please mark brainliest and have a great day!
Answer:
2500
Step-by-step explanation:
Answer:
The answer is y = -3x + 7.
Step-by-step explanation:
❃Incase you forgot what the linear equation formula is ☟
![y = mx + b](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20b)
❃Incase you also forgot, what the slope formula is ☟
![m = \frac{y_2 - y_1}{x_2 - x_1}](https://tex.z-dn.net/?f=m%20%3D%20%20%5Cfrac%7By_2%20-%20y_1%7D%7Bx_2%20-%20x_1%7D%20)
➊ First: We are going to be solving for the slope.
![m = \frac{ - 8 - 1}{5 - 2} = \frac{ - 9}{ \: \: \: 3} = - 3](https://tex.z-dn.net/?f=m%20%3D%20%20%5Cfrac%7B%20-%208%20-%201%7D%7B5%20-%202%7D%20%20%3D%20%20%5Cfrac%7B%20-%209%7D%7B%20%5C%3A%20%20%5C%3A%20%20%5C%3A%203%7D%20%20%3D%20%20-%203)
➋Second: We find the y-intercept.
![y = mx + b \\ 1 = - 3(2) + b \\ 1 = - 6 + b \\ \frac{ + 6 = + 6 \: \: \: \: \: \: \: \: \: }{7 = b}](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20b%20%5C%5C%201%20%3D%20-%203%282%29%20%2B%20b%20%5C%5C%201%20%3D%20-%206%20%2B%20b%20%5C%5C%20%5Cfrac%7B%20%2B%206%20%3D%20%2B%206%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%7D%7B7%20%3D%20b%7D)
➌Third: Plug in.
![y = - 3x + 7](https://tex.z-dn.net/?f=y%20%3D%20%20-%203x%20%2B%207)
I believe the X-coordinate of the midpoint would be (0.5,-0.5)